2018
DOI: 10.1155/2018/2951928
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Allergic Rhinitis and Laryngopharyngeal Reflux

Abstract: Background and Objectives Laryngopharyngeal reflux (LPR) exhibits nonspecific clinical presentations, and these symptoms may be associated with other conditions such as allergies, including allergic rhinitis and laryngitis. However, there is a gap in the literature regarding the correlation of laryngopharyngeal reflux with allergic rhinitis/laryngitis. Hence, the aim of this study is to explore the correlation between these two conditions. Patients and Methods A total of 126 patients with suggestive manifestat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 35 publications
2
20
0
1
Order By: Relevance
“…A causal link between GORD and AR was not established and only a few studies indicated a correlation [42]. We found in our study that LPR and AR occurred simultaneously more frequently as having LPR increased the incidence for AR by more than two folds which is similar to other studies [17,18]. Having asthma increased the correlation, but the correlation persisted even when excluding asthma which concurs with another study [18].…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…A causal link between GORD and AR was not established and only a few studies indicated a correlation [42]. We found in our study that LPR and AR occurred simultaneously more frequently as having LPR increased the incidence for AR by more than two folds which is similar to other studies [17,18]. Having asthma increased the correlation, but the correlation persisted even when excluding asthma which concurs with another study [18].…”
Section: Discussionsupporting
confidence: 89%
“…GORD in addition to Rhinitis in general are among the main causes of chronic cough, and their role has been discussed in several studies; increased reoccurrence of the cough with reflux symptom has also been reported in more than a few patients with GORD and in those with rhinitis who do not have symptoms of GORD, indicating that other factors contribute to the development of chronic cough. In addition, the coexistence of GORD and chronic rhinosinusitis (CRS) were reported by multiple studies [17,18,41,42,45,46]. One theory explaining this phenomena is that Helicobacter pylori, which is usually found in the gastric mucosa and promotes heartburning, can exist in the sinonasal cavity [47].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many GERD patients experience dysmotility and prolonged acidity when the lower esophageal sphincter malfunctions, thereby allowing stomach acid to move up the esophagus, causing heartburn [12,18]. LPR is associated with a failure of the upper sphincters, which allows the acid to move up to the throat and even into the nose or middle ears [7][8][9]12]. LPR patients commonly present tissue damage of the laryngopharyngeal epithelium [12,19].…”
mentioning
confidence: 99%